THE IMPACT OF SPIRITUAL LEADERSHIP PERCEPTION ON PHYSICAL EDUCATION TEACHERS’ INNOVATION IN UNIVERSITIES IN CHINA - Xiang, Cheng; Wang, Hsuan-Po (Veredas do Direito, 2026)
Physical education teachers play a unique role in the university environment. They need to not only teach physical skills, but also cultivate students’ teamwork spirit and physical fitness, thereby playing a crucial role in higher education. This study used the questionnaire survey method, taking physical education teachers in Chinese universities as samples. A total of 554 formal questionnaires were collected. This study aims to explore predictive effects of perceived spiritual leadership of physical education teachers in Chinese universities on teachers’ innovation, and the mediating effect of workplace spirituality between perceived spiritual leadership and innovative behaviors. The results indicate that there are no significant differences in teachers’ innovative behaviors among physical education teachers of different genders, while there are significant differences among teachers with different educational backgrounds and professional titles. Perceived spiritual leadership has a significant positive impact on teachers’ innovative behaviors and workplace spirituality; workplace spirituality has a significant positive influence on teachers’ innovative behaviors; and workplace spirituality has a mediating effect between the perceived spiritual leadership and teachers’ innovative behaviors. This study provides practical guidance for university administrators by exploring the impact of perceived spiritual leadership on the innovative behaviors of physical education teachers in universities.